A Latent Profile Analysis of Santri’s Reading Attitude and Reading Motivation - Murtafi’ah, B; Pancoro Setyo Putro, N H (KnE Social Sciences, 2019)
The issue of students’ reading attitude and reading motivation has received considerable critical attention over decades. However, there is a notable paucity of similar study describing reading attitude and motivation profiles in the context of santris or students in Islamic boarding schools. This study set out to investigate the profile of santris’ reading attitude and motivation in the disruptive era. Three hundred and nineteen (319) students participated in this study by completing both reading attitude questionnaires adapted from McKenna et al. (2012) and motivational reading questionnaire (MRQ) adapted from Wigfield and Guthrie (1997). Latent profile analysis (LPA) with Mplus 7.4 was used to identify the students latent profile in reading attitude and motivation. A 2-profile solution provided the best fit to the data. Class 1 was characterized by relatively low reading attitude and reading motivation among santri. On the other hand, Class 2 was associated with santri with higher level of reading attitude and reading motivation than Class 1. The present study, therefore, revealed that there may be different profiles of reading attitude and reading motivation specifically for santri in English lesson. Keywords: latent profile analysis, santri, reading attitude, reading motivation